Early life stress sensitizes individuals to the psychological correlates of mild fluctuations in inflammation. Issue 3 (6th September 2019) - Kuhlman, Kate R.; Robles, Theodore F.; Haydon, Marcie D.; Dooley, Larissa; Boyle, Chloe C.; Bower, Julienne E.
Abstract: Background: Early life stress (ELS) has been linked to health disparities across the human lifespan, particularly increased risk for depression and its recurrence. In this study we explore two plausible and competing pathways through which ELS may lead to depression via inflammation. Methods: Participants (ages 18–22; n  = 41) completed the Early Trauma Inventory as a measure of ELS. Participants then completed consecutive daily diaries of mood and other sickness behavior for the 7 days prior to and 7 days after receiving the annual influenza vaccine. Circulating concentrations of plasma interleukin‐6 (IL‐6) were measured immediately before and 24 hr after vaccination. Results: ELS was not associated with the magnitude of change in IL‐6 from pre‐ to post‐vaccine, however, exposure to ELS moderated the association between change in IL‐6 from pre‐ to post‐vaccine and changes in both cognitive difficulty and depressed mood. Individuals exposed to greater ELS showed greater psychological sensitivity to increases in IL‐6. Conclusions: Exposure to ELS may increase sensitivity to peripheral inflammation in the central nervous system. Future studies elaborating on the impact of ELS on the sensitivity of specific neural circuits and cells to inflammation are needed.